Enhancing Collaboration Between 3D Artists and Programmers in Game Development with Agile Practices - Machado, Lucas Rister; Rutzig, Mateus Beck; Fontoura, Lisandra Manzoni (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2024: Anais do XXIII Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2024.240512, 2024)
Game development differs from traditional software flow since it should align stakeholders' needs with 3D artist and programmer teams. Stakeholders' requirements, such as high-quality 3D models and new functionalities, conflict with the constraints that programmers should deal with, such as hardware graphics processing limitations and resource optimization, which can increase project costs and time to market. In this work, we propose the employment of a set of agile practices to facilitate the development of 3D assets that, in addition to satisfying the demands of stakeholders, also address the requirements and constraints of the 3D artist and programmer team. Results show that the proposed practices have reduced the time to respond to new requests or modification of assets, avoiding redoing tasks and wasting developer time.